2017
DOI: 10.1002/jcp.26111
|View full text |Cite
|
Sign up to set email alerts
|

GSK‐3β inhibition suppresses instability‐induced osteolysis by a dual action on osteoblast and osteoclast differentiation

Abstract: Currently, there are no medications available to treat aseptic loosening of orthopedic implants. Using osteoprotegerin fusion protein (OPG-Fc), we previously blocked instability-induced osteoclast differentiation and peri-prosthetic osteolysis. Wnt/β-catenin signaling, which regulates OPG secretion from osteoblasts, also modulates the bone tissue response to mechanical loading. We hypothesized that activating Wnt/β-catenin signaling by inhibiting glycogen synthase kinase-3β (GSK-3β) would reduce instability-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…With reference to a previous study, miRNAs have regulatory functions on multiple components of Wnt signaling pathway . Also, it has been indicated that the Wnt signaling pathway plays an important role in the regulation of both osteoblast and osteoclast differentiation . The crucial step of Wnt signaling pathway is the degradation of cytosolic β‐catenin by the APC/AXIN1 destruction complex, and Wnt signaling inhibits β‐catenin ubiquitination normally occurring within the complex, resulting in complex saturation through an accumulation of phospho‐β‐catenin .…”
Section: Discussionmentioning
confidence: 98%
“…With reference to a previous study, miRNAs have regulatory functions on multiple components of Wnt signaling pathway . Also, it has been indicated that the Wnt signaling pathway plays an important role in the regulation of both osteoblast and osteoclast differentiation . The crucial step of Wnt signaling pathway is the degradation of cytosolic β‐catenin by the APC/AXIN1 destruction complex, and Wnt signaling inhibits β‐catenin ubiquitination normally occurring within the complex, resulting in complex saturation through an accumulation of phospho‐β‐catenin .…”
Section: Discussionmentioning
confidence: 98%
“…These results further implicate the GSK-3β/β-catenin signaling pathway as a mediator of Ti particle-induced osteolysis. A recent study showed that modulation of Wnt/β-catenin and BMP-2 signaling with GSK-3β inhibitor AR28 accelerated bone repair, up-regulated osteoblast differentiation, and attenuated osteoclastogenesis via an OPGassociated mechanism in a rat model of instability-induced osteolysis (Amirhosseini et al, 2017).…”
Section: Signaling Pathways In Wear Debris-activated Osteoblastsmentioning
confidence: 99%
“…It has been reported to play a role in regulating a variety of cellular responses, including cell growth, migration, tumorigenesis and cytokine production [26]. Amirhosseini et al reported that inhibition of GSK3B could regulate osteoblast and osteoclast differentiation to suppress instable-induced osteolysis and bone loss by activating Wnt /β-catenin signaling [27]. In addition, Jang et al demonstrated a novel role for GSK3B…”
Section: Discussionmentioning
confidence: 99%